Creatividad e inteligencia - Sternberg, Robert J. (CIC. Cuadernos de Información y Comunicación, 2005)
A review of the most important theories and studies about intelligence and creativity. Both human abilities are considered from the different perspectives of relation, from inclusive ones to separate categories. The author shows us the variety and depth of present analysis that study creativity as a vital element to open new stances of cognitive world. The author exposes his essential triarchic intelligence theory.
Keywords: intelligence and creativity; studies of creativity; Sternberg’ s theory triarchic of intelligence